CLINICO-PATHOLOGICAL STUDY OF CONTAGIOUS CAPRINE PLEUROPNEUMONIA (CC PP) I N SMALL RUMINANTS - U. Sadique; Z. I. Chaudhry; M. Younus; A. A. Anjum; M. Idrees M. S. Qureshi; A. Sajid; Z. U. Hassan; M. Mushtaq; S. M. Subtain (Journal of Animal and Plant Sciences, 2012)
This study was conducted to determine clinico-pathological manifestation of contagious Caprine pleuropneumonia (CCPP) in field outbreak in Kyber Pakhtunkhwa. A total of 120 samples were collected from goats exhibiting clinical signs of pneumonia suspected for CCPP during disease out break in field in different regions [northern (NR), central (CR) and southern(SR)] of Khyber Pakhtunkhwa Pakistan. All physical and clinical parameters of animals were examined and detail observations were documented. The predominant clinical findings include pyrexia (NR 80%, CN 83%, SR 69%), cough (NR 78%, CN 70%, SR 72%), excessive lacremation (NR 70%, CN 72%, SR 69%), nasal discharges catarrhal initially turned into mucopurulent in the advance stage, unilateral and bilateral conjunctivitis with corneal opacity, dysponia, abduction of the elbow and diarrhea. The majority (83 %) of animals presented pathological lesions in the form of consolidation (NR 83%, CN 87%, and SR 79%) and marbled appearance of lungs with fibrinopurulent membrane on pleural surface. Straw colored pleural fluid was present in pleural cavity with pleural adhesion (NR 39%, CN 43%, SR 51%), hydro pericardial fluid in pericardial sac, necrotic foci on surface of the liver and pus in the pelvis of kidneys. Microscopic lesions characteristic of CCPP i.e., pulmonary emphysema, atelactasis and thickening of interlobular septa were found in almost all cases. Widespread lesions in different organs of the infected animals and the septicemic nature of the disease suggest Mycoplasma mycoides Capri (Mmc) is the causative agent of CCPP
Keywords: Contagious Caprine pleuropneumonia; Mycoplasma mycoides Capri; clinico-pathological